2020
DOI: 10.1097/md.0000000000019527
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic cognitive enhancers for improvement of cognitive function in patients undergoing electroconvulsive therapy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(37 reference statements)
1
5
0
1
Order By: Relevance
“…In the donepezil group, faster post-ECT cognitive recovery was observed in comparison to the placebo group. In line with our study, a meta-analysis indicated that cognitive enhancers might improve cognitive function and decrease cognitive side-effects induced by ECT (25).…”
Section: Discussionsupporting
confidence: 91%
“…In the donepezil group, faster post-ECT cognitive recovery was observed in comparison to the placebo group. In line with our study, a meta-analysis indicated that cognitive enhancers might improve cognitive function and decrease cognitive side-effects induced by ECT (25).…”
Section: Discussionsupporting
confidence: 91%
“…These AEs may be seizure-related, such as prolonged and tardive seizures and status epilepticus, AEs due to muscle relaxants such as prolonged apnea, malignant hypothermia, hyperkalemia, and awareness of neuromuscular paralysis, cardiovascular AEs, such as asystole, raised blood pressure, myocardial infarction, and cardiomyopathy, as well as cognitive AEs such as amnesia and memory loss ( Andrade et al, 2016 ). Regarding the widespread experience of disabled cognition after ECT, it has been proven extensively that ECT may cause cognitive dysfunction but that this condition is reversible and not life-threatening ( Semkovska and McLoughlin, 2010 ; Ziegelmayer et al, 2017 ; Landry et al, 2021 ), and that cognitive enhancer may reduce ECT-induced cognitive side effects ( Niu et al, 2020 ). Meta-analyses suggest that new learning is impaired immediately following ECT but that group means to return at least to baseline by 14 days after ECT.…”
Section: Discussionmentioning
confidence: 99%
“…Wynik chińskiego badania z 2020 roku przeprowadzonego prze Niu i wsp. [47] wskazał na możliwość zastosowania memantyny jako środka już nie tylko doraźnego, ale profilaktycznego po procedurze EW [47]. W tym samym roku w irańskim badaniu porównano zastosowanie memantyny z melatoniną, zdecydowanie wskazując na tą pierwszą pod kątem łagodzenia deficytów poznawczych [48].…”
Section: Możliwości łAgodzenia Zaburzeń Poznawczych Po Ewunclassified